The alchemy of the mathematics curriculum: inscriptions and the fabrication of the child - Popkewitz, Thomas (American educational research journal, 2004)
School subjects are analogous to medieval alchemy. There is a magical change as mathematics, science, and social sciences move from their disciplinary spaces into the classroom. The educational and social psychologies have little or nothing to do with understanding disciplinary practices. They are intellectual inventions for normalizing and governing the child's conduct, relationships, and communications. The author examines the alchemy in standard-based mathematics educational policy and research for K-12 schools. He argues that (a) the emphasis on "problem solving", collaborating, and "communities of learning" sanctify science and scientists as possessing authoritative knowledge over increasing realms of human phenomena, thus narrowing the boundaries of possible action and critical thought; and (b) while reforms stress the need for educational equity for "all children", with "no child left behind, the pedagogical models divide, demarcate, and exclude particular children from participation. (DIPF/Orig.).